Quantitative collateral score for the prediction of clinical outcomes in stroke patients: Better than visual grading - Lu, Qingqing; Zhang, Haiyan; Cao, Xin; Fu, Junyan; Pan, Yuning; Zheng, Xiaodong; Wang, Jianhong; Geng, Daoying; Zhang, Jun (Frontiers in Neuroscience, 2022)
Objectives: To identify preoperative prognostic factors for acute ischemic stroke (AIS) patients receiving mechanical thrombectomy (MT) and compare the performance of quantitative collateral score (qCS) and visual collateral score (vCS) in outcome prediction. Methods: Fifty-five patients with AIS receiving MT were retrospectively enrolled. qCS was defined as the percentage of the volume of collaterals of both hemispheres. Based on the dichotomous outcome assessed using a 90-day modified Rankin Scale, we compared qCS, vCS, age, sex, National Institute of Health stroke scale score, etiological subtype, platelet count, international normalized ratio, glucose levels, and low-density lipoprotein cholesterol (LDL-C) levels between favorable and unfavorable outcome groups. Logistic regression analysis was performed to determine the effect on the clinical outcome. The discriminatory power of qCS, vCS, and their combination with cofounders for determining favorable outcomes was tested with the area under the receiver-operating characteristic curve (AUC). Results: vCS, qCS, LDL-C and age could all predict clinical outcomes. qCS is superior over vCS in predicting favorable outcomes with a relatively higher AUC value (qCS vs. vCS: 0.81 vs. 0.74) and a higher sensitivity rate (qCS vs. vCS: 72.7% vs. 40.9%). The prediction power of qCS+LDL-C+age was best with an AUC value of 0.91, but the accuracy was just increased slightly compared to that of qCS alone. Conclusions: Collateral scores, LDL-C and age were independent prognostic predictors for patients with AIS receiving MT; qCS was a better predictor than vCS. Furthermore, qCS+LDL-C+age offers a strong prognostic prediction power and qCS alone was another good choice for predicting clinical outcome.